2016
DOI: 10.1159/000449031
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Comparison of Allogeneic versus Autologous Stem Cell Transplantation in Transformed Low-Grade Lymphoid Malignancies: A Systematic Review and Pooled Analysis of Comparative Studies

Abstract: Background: Some patientswith low-grade lymphoid malignancies develop transformed disease, requiring stem cell transplantation (SCT). SCT outcomes in transformed low-grade lymphoid malignancies may differ from those of nontransformed disease or other aggressive non-Hodgkin lymphomas. We conducted a pooled analysis of the clinical outcomes of allogeneic versus high-dose therapy (HDT) with autologous SCT in adult patients with transformed low-grade lymphoid malignancies. Methods: A PubMed, EMBASE, and Cochrane s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…However, in terms of clinical outcome, the response of allogeneic therapy for nonresponsive FCGS appears to be delayed as compared to autologous ASC treatment. No direct comparison to other studies is possible; however, other studies also demonstrated improved outcome when using an autologous cell source as compared to allogeneic . This delayed response has practical implications when performing a clinical trial in a debilitating and painful disease, such as FCGS, as cat‐owner satisfaction and compliance depend on response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, in terms of clinical outcome, the response of allogeneic therapy for nonresponsive FCGS appears to be delayed as compared to autologous ASC treatment. No direct comparison to other studies is possible; however, other studies also demonstrated improved outcome when using an autologous cell source as compared to allogeneic . This delayed response has practical implications when performing a clinical trial in a debilitating and painful disease, such as FCGS, as cat‐owner satisfaction and compliance depend on response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there are no established standards of care for patients with clonally related DLBCL-RS, and a clinical trial should thus always be considered. If a clinical trial is unavailable, the most appropriate therapeutic interventions currently appear to be induction treatment with immunochemotherapy followed by postremission consolidation with allogeneic or (if not feasible) autologous hematopoietic stem cell transplantation (HSCT) 18,72,73. In a large retrospective analysis of the European Group for Blood and Marrow Transplantation, the median OS, relapse-free survival, and the cumulative incidences of relapse and nonrelapse mortality at 3 years for patients with RS undergoing allogeneic HSCT were 36%, 27%, 47%, and 26%, respectively, while they were 59%, 45%, 43%, and 12%, respectively, for RS patients undergoing autologous HSCT 73…”
Section: Biology and Features Of Dlbcl-rsmentioning
confidence: 99%
“…Patients with chemotherapy sensitive disease who achieved a CR with ASCT had an 84% 4-year survival compared to 44% with patients who had partial response (PR). There are several trials that continue to evaluate the role of ASCT or allo-SCT [13,14] as well as tandem transplantation [15] for aggressive lymphoma. In a study by Taverna and colleagues (2016) relapse prevention strategies after ASCT consolidation were reviewed in great detail [16].…”
Section: Introductionmentioning
confidence: 99%